MICROSCÓPIO USB DE BAIXO CUSTO NO LABORATÓRIO DIDÁTICO DE ELETROQUÍMICA: DOIS EXPERIMENTOS CLÁSSICOS SOB UM NOVO (MICRO) OLHAR - Aline Samara Lima de Jesus; Emerson Costa Rios; Ana Cláudia Kasseboehmer; Ettore Paredes Antunes (Química Nova)
This research addresses the importance of introducing students to the scientist’s methods of thinking and acting in science teaching. We highlight two sets of science skills related to collecting and analyzing data, and communicating scientific ideas. The innovation is the use of a low cost digital microscope with a USB (universal serial bus) interface to monitor the experimental activities of steel corrosion and water electrolysis in the context of teaching electrochemistry in a physical chemistry graduation course. Thirty-three students from the chemical engineering course at a university in Northern Brazil participated in this research, who were studying the discipline, arranged in groups. The results show that the students performed well in the scientific skills assessed during the steel corrosion experiment due to the apparatus. However, in the water electrolysis experiment, there were more difficulties, especially in communicating scientific ideas. Participants reported that using the microscope helped them understand chemical phenomena and increased curiosity and learning. It highlights the importance of the pedagogical approach based on experimental activities, which are similar to the practices of science, allowing students to be active agents in the construction of knowledge and the use of the low cost digital microscope as an innovative tool in teaching electrochemistry.